Pertanggungjawaban Pidana Berdasarkan Teori Penyertaan (Deelneming) dalam Pemberian Kredit Bermasalah pada Bank Pembangunan Daerah: Studi Putusan Nomor 38/Pid.Sus-TPK/2023/PN Kpg Jo. Nomor 3/Pid.Sus-TPK/2024/PT KPG Jo. Nomor 5388 K/Pid.Sus/2024 - Alberth Nixon Bria; Aksi Sinurat; Orpa Juliana Nubatonis (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study analyzes the implementation of the Deelneming theory as a basis for imposing criminal liability on parties involved in the granting of non-performing loans that resulted in state financial losses at the Regional Development Bank of East Nusa Tenggara. The study is motivated by the fact that criminal liability in banking corruption cases is often focused solely on credit analysts, despite the collective decision-making process involving multiple officials with distinct authorities. This research employs a normative juridical method using statutory, conceptual, and case approaches. The primary legal materials consist of laws and regulations governing banking, corruption, and criminal law, while secondary legal materials include court decisions, legal doctrines, and relevant scientific literature. The findings indicate that non-performing loans are fundamentally part of banking business risk but may transform into corruption when the credit approval process violates the prudential principle, involves abuse of authority, and causes state financial losses. The study further reveals that the Deelneming doctrine provides a normative basis for extending criminal liability to all parties who substantially contribute to unlawful credit approval. Therefore, harmonization between banking law and anti-corruption law is necessary to establish clear legal parameters distinguishing legitimate business risk from criminal conduct while strengthening legal certainty and effective law enforcement in the banking sector.